PERSONAL BRANDING ANALYSIS MUHAMMAD ZHARIF DARY KURAHMAN ON TIKTOK ACCOUNT @zharif.dk AS HEALTHY LIFESTYLE INFLUENCER - Ratu Maziatul Hikmah; Andika Witono; Agatha Amalia Putri (JURNAL SIGNAL, 2025)
Personal branding is the process of showcasing an individual's unique skills, personality, and character to build a distinctive and recognizable identity. This concept applies not only to products or services but can also be utilized by individuals as a means to influence public perception and shape the desired image of themselves. The primary goal of personal branding is to create an authentic and relevant impression that can be recognized and remembered by others. This research aims to deeply examine the personal branding of Muhammad Zharif Dary Kurahman as a health lifestyle influencer through his TikTok account, @zharif.dk. Utilizing a descriptive qualitative methodology, this study analyzes Zharif's branding strategies based on the eight laws of personal branding proposed by Peter Montoya (The Eight Laws of Personal Branding). Data was gathered through primary sources, including observations and in-depth interviews, while supporting data was obtained from relevant literature, journals, and articles. The findings reveal that Zharif has successfully established himself as an influencer in the fields of bodybuilding and healthy living. Additionally, his empathetic personality is reflected in content that emphasizes social responsibility. Based on the research results, it is recommended that Zharif maintain greater consistency in showcasing the elements of his personal branding, particularly in terms of perseverance and content sustainability. This consistency will strengthen his identity as an influencer, making it easier for audiences to remember and relate to him.